The Modern Trends of Economic Relations Between Iraq and China for the Period 2010 -2023 - Hamid Awakhti Ali, Salar; Foad Abdulla Ahmed , Pana (Journal of Economics and Administrative Sciences, 2024)
Purpose: The study aims to analyze and understand the economic relations between Iraq and China in the modern era, providing insights into their development, current status, and future prospects. It seeks to identify the key factors influencing these relations and to evaluate the impact of trade, investment, and geopolitical strategies on bilateral economic ties. Additionally, the study aims to offer a nuanced understanding of the challenges and opportunities present in the Iraq-China economic partnership. Theoretical Framework: The study utilizes frameworks that explain bilateral economic relations, including theories on trade, investment, and geopolitical influence. It integrates insights and data from studies such as Shanshool (2022), Gul (2022), Wuthnow (2017), and Shareef (2016), providing a foundation for understanding the economic dynamics between Iraq and China. Design/Methodology/Approach: A mixed-method approach was employed, combining qualitative and quantitative analyses with a historical examination of bilateral relations between Iraq and China. Data were gathered from sources such as the Observatory of Economic Complexity (2022) for China (CHN) and Iraq (IRQ), as well as academic databases including PubMed, Scopus, Web of Science, and Google Scholar to complement the financial and economic data with relevant literature. E-Views statistical software was utilized for data analysis. Linear correlation was applied to evaluate the strength and direction of relationships, with complemented by tests such as the Jarque-Bera Test, ADF Test, UR Test, Causality analysis, Cointegration, and the BPG Test. Findings: The study provides insights into the historical development of Iraq-China relations, highlighting the challenges such as oil price volatility and political obstacles. The findings offer a detailed understanding of the contemporary economic relations between Iraq and China. Research, Practical & Social Implications: Practical implications include recommendations for policymakers to strengthen infrastructure, streamline bureaucratic processes, and diversify investments beyond the oil sector. The study’s insights can aid in formulating policies that enhance bilateral economic cooperation and address the identified challenges. Originality/Value: The originality and value of the study lie in its comprehensive analysis of contemporary Iraq-China economic relations. It explores less-studied areas such as technological cooperation and provides practical recommendations for fostering stronger economic ties. The study’s mixed-methods approach, and the use of various statistical tools ensure a robust analysis of the bilateral economic dynamics.